Evaluation of performance of RCC-T girder bridge by varying girder configuration and span length - Kandel, Sadiksha; Suwal, Rajan; Bastola, Subash (Journal of Engineering Issues and Solutions, 2026)
Reinforced Concrete-T girder bridges are generally constructed in Nepal because of their suitability and adaptability to medium span range from 10 m to 25 m. The behavior and performance of such bridge depends on variations of parameters. Therefore, there is need of parametric study to understand how these different parameters influence the behavior (stress and deflection) that helps to identify the possible weaknesses. Parametric studies analyze stress and strain distribution, assess the dynamic performance that helps to determine material efficiency, costs, and durability which contribute to bridge lifespan. This research mention parametric variation by considering changes of span length and number of girders. The motive behind this study is to find out the behavior of bridge (stress and deflection) by varying the span length and number of girders, also to determine impact of dynamic load on bridge and to calculate how number of girders will affect economy and behavior of bridge. The study was conducted by following static and dynamic analysis using FEM software CSiBridge V24.2.0 along with economic implication implementing MCDA approach on python. Dead load, Live load IRC Class A vehicular load was used to perform static and dynamic analysis. The findings of this study shows that under equivalent deflection, compressive stress is higher in three-girder system while tensile stress dominates in two-girder system suggesting that two-girder system performs better structurally and it is economical by reducing cost from 7.5% to 5.9% at shorter span and three-girder performs better at longer span with being the most economical choice by reducing cost up to 4.68%. Along with it, Dynamic Amplification Factor (DAF) was also determined to know how much structure gets amplified. The result stated that both stress and deflection gets more amplified when bridge is subjected to dynamic load and compressive stress seems to be more amplified compared to tensile stress and deflection.